Pulsed-field gel electrophoresis, pertactin, pertussis toxin S1 subunit polymorphisms, and surfaceome analysis of vaccine and clinical Bordetella pertussis strains - Bottero, Daniela (2007)
To add new insight to our previous work on the molecular epidemiology of Bordetella pertussis in Argentina, the prn and ptxS1 gene sequences and pulsed-field gel electrophoresis (PFGE) profiles of 57 clinical isolates obtained during two periods, 1969 to 1989 and 1997 to 2006, were analyzed. Non-vaccine-type ptxS1A was detected in isolates obtained since 1969. From 1989 on, a shift of predominance from the vaccine prn1 type to the nonvaccine prn2 type was observed. This was also reflected in a transition of PFGE group IV to group VI. These results show that nonvaccine B. pertussis strains are currently circulating. To analyze whether the observed genomic divergences between vaccine strains and clinical isolates have functional implications, protection assays using the intranasal mouse challenge model were performed. For such experiments, the clinical isolate B. pertussis 106 was selected as representative of circulating bacteria, since it came from the major group of the PFGE dendrogram (PFGE group VI). Groups of mice were immunized either with diphtheria-tetanus- whole-cell pertussis vaccine (ptxS1B prn1) or a vaccine prepared by us containing B. pertussis 106. Immunized mice were then challenged with a B. pertussis vaccine strain (Tohama, harboring ptxS1B and prn1) or the clinical isolate B. pertussis 106 (ptxS1A prn2). An adequate bacterial-elimination rate was observed only when mice were immunized and challenged with the same kind of strain. For further characterization, comparative proteomic profiling of enriched membrane proteins was done using three vaccine strains and the selected B. pertussis 106 clinical isolate. By matrix-assisted laser desorption ionization-time of flight mass spectrometry analysis, a total of 54 proteins were identified. This methodology allowed us to detect differing proteins among the four strains studied and, in particular, to distinguish the three vaccine strains from each other, as well as the vaccine strains from the clinical isolate. The differing proteins observed have cellular roles associated with amino acid and carbohydrate transport and metabolism. Some of them have been proposed as novel vaccine candidate proteins for other pathogens. Overall, the global strategy described here is presented as a good tool for the development of next-generation acellular vaccines.